Blockade of voltage-gated K+ currents in rat mesenteric arterial smooth muscle cells by MK801 - Jeong Min Kim; Sang Woong Park; Hai Yue Lin; Kyung Chul Shin; Dong Jun Sung; Jae Gon Kim; Hana Cho; Bokyung Kim; Young Min Bae (Elsevier, 2015)
MK801 (dizocilpine), a phencyclidine (PCP) derivative, is a potent noncompetitive antagonist of the N-Methyl-D-aspartate receptor (NMDAr). Another PCP derivative, ketamine, was reported to block voltage-gated K+ (Kv) channels, which was independent of NMDAr function. Kv currents are major regulators of the membrane potential (Em) and excitability of muscles and neurons. Here, we investigated the effect of MK801 on the Kv channels and Em in rat mesenteric arterial smooth muscle cells (RMASMCs). We used the whole-cell patch clamp technique to analyze the effect of MK801 enantiomers on Kv channels and Em. (+)MK801 inhibited Kv channels in a concentration-dependent manner (IC50 of 89.1 ± 13.1 μM, Hill coefficient of 1.05 ± 0.08). The inhibition was voltage- and state- independent. (+)MK801 didn't influence steady-state activation and inactivation of Kv channels. (+)MK801 treatment depolarized Em in a concentration-dependent manner and concomitantly decreased membrane conductance. (−)MK801 also similarly inhibited the Kv channels (IC50 of 134.0 ± 17.5 μM, Hill coefficient of 0.87 ± 0.09). These results indicate that MK801 directly inhibits the Kv channel in a state-independent manner in RMASMCs. This MK801-mediated inhibition of Kv channels should be considered when assessing the various pharmacological effects produced by MK801, such as schizophrenia, neuroprotection, and hypertension.